Etude Préliminaire De La Valorisation Des Tourteaux D’hévéa, D’anacarde Et De Pourghère Chez Les Porcs Durant La Gestation Et La Lactation - Alain, Kone Gningnini; Vincent, KouakouN’Goran David; Monique, Angbo-KouakouCho Euphrasie; Bertin, Kouame Kouadio; François de Paul, Yeboue; Maryline, Kouba (European Scientific Journal, ESJ, 2016)
The enhancement the cake of cashew kernels downgraded (Anacardium occidentale) (TA), the detoxified cake of kernels rubber (Hevea brasiliensis) (TH) and jatropha (Jatropha curcas) (TJ) in pig feed, was study on 21 pregnant gilts (73.4±8.1 kg). These females randomly distributed by group of three, received control diet (RT) and six other diets containing 7.5% or 15% of TA (RTA7.5 and RTA15), 7.5% or 15% of TH (RTH7.5 and RTH15) or 7.5% or 15% of TJ (RTJ7.5 and RTJ15). During the trial of 152 days, gilts under RTJ15 regime and two gilts under RTJ7.5 regime were withdrawn after respectively 14 and 21 days’ supply due to a persistent diarrhea. The latest gilt under RTJ7.5 had aborted at 90 days of gestation. No significant difference was observed on the average litter size (9.2 piglets). The average weight of piglets at birth ranged from 1.3±0.2 kg (RTA15) and 1.1±0.2 kg (RTH7.5), while the average daily gain (ADG) of